Lactic Acid Levels Yogurt Red Beans with Addition of Honey Trigona sp - Ruri Widyati; Neni Oktiyani; Haitami Haitami (Baiman Bauntung Batuah Center, 2019)
Red beans (Phaseolus vulgaris L.) are grains that are rich in nutrients and useful as a substitute for vegetable milk which can be processed into yogurt using Streptococcus thermophillus and Lactobacillus bulgaricus. Carbohydrates in red beans consist of a group of oligosaccharides that have little ability as an energy source for bacteria to produce lactic acid. Therefore, the making of red bean yogurt needs another source of sugar by adding Trigona sp. Honey. The purpose of this study was to determine the effect of adding Trigona sp honey by 0%, 1.9%, 3.8%, 5.7%, 7.6%, 9.5% to the total level of lactic acid in red bean yogurt incubated for 24 hours at 37oC. This type of research is an experiment with the Postest Only With Control Group Design research design using the alkalimetry titration method. The sampling technique used was purposive sampling technique, namely Trigona sp honey bee taken at Trigona sp bee farm in Tambangan, Tanah Laut. Indonesia. The results showed that there was an effect of adding Trigona sp honey to total lactic acid levels in red bean yogurt with the addition of Trigona sp honey 1.9% - 9.5% fulfilling the requirements of SNI 01.2981-2009. The highest average value of total lactic acid in red bean yogurt with the addition of Trigona sp honey 9.5% which is equal to 0.6672%. It is recommended for future researchers to use other types of carbohydrate sources and additives in the form of proteins. For the community, it is recommended to use alternative sources of other sugar and optimize the addition of Trigona sp. Honey.